[Mrs. István Altner 1]
negative films writing on type-writer, playing music, positive, car on the road among mountains, woman with 2 dogs, walking among ruins (Italy?), musicians, traffic in the city, on a building:Voyageurs, bridge across a big valley, cows on the moutain, waterfall, on a stone: Oued Rhumel, nice rocks, tunnel, train, details from a westerns, cartoons, combination of actor & cartoon figure, "Made in Bailey filstudio", film-detail with german notices "La race Jaune", every-day life of Chinese people, interesting hydroplan "Dornier" taking flight & landing,details from a Harold Lloyd film with German notices